People on probation as an inclusion health group: Exploring needs, barriers and service provision in Wales - Rabaiotti, Ella (Probation journal, 2024)
People on probation face particular health inequalities and are categorised as an ‘inclusion health’ population group within public health policy in Wales. The health of this group is thought to be worse than the general population and a factor in whether people reoffend. This article is based on mixed-methods exploratory research which included a survey covering 34 community-based services who work with people on probation across Wales. Survey respondents indicated service availability and waiting lists, and mistrust of professionals are key barriers to accessing healthcare. The most identified health needs were mental health and substance misuse related. There is an opportunity to increase the focus on healthcare for people on probation through inclusion health approaches.